On the Romanisation of the Vilniusites, or What Cicero Is Doing in the Municipal Statutes of 1620 - Urmański, Antoni K. (Senoji Lietuvos literatūra, 2025)
The article seeks to answer the question of why two maxims by Cicero were included at the beginning of the municipal statutes of Vilnius of 1620 and what they meant for the self-image of the Vilniusites. It is proposed that these quotations are not merely an aesthetic embellishment but also a manifestation of humanistic and civic values. Their emergence is linked to the figure of Augustinus Rotundus, the vogt of Vilnius. It is likely that Rotundus, who was a prominent Lithuanian humanist, an expert in Roman law, and an admirer of Cicero’s works, was also the author of the first edition (1551) of the municipal statutes. This article examines the reception of Cicero in the Grand Duchy of Lithuania, Rotundus’s studies at European universities, his literary and legal activities, and his contribution to the formation of the Lithuanians’ Roman political and cultural identity. It is shown that Rotundus’s Ciceronian humanism manifested itself through his advocacy of freedom, the rule of law, civic responsibility, the significance of history, and the importance of education. Emphasis is also placed on the role of the vogt of Vilnius in establishing the Jesuit College of Vilnius, which became the most important centre for the dissemination of Latin culture and Cicero’s literary legacy in Lithuania. The article concludes that Cicero’s maxims in the municipal statutes attest to the Romanisation of the urban elite of Vilnius, their desire to identify with the humanistic values of the republic, and, possibly, their wish to honour Rotundus as the shaper of their city’s legal and cultural identity.
Keywords: Augustinus Rotundus; Cicero; Vilnius Jesuit College; municipal statutes of Vilnius